2009
DOI: 10.1038/modpathol.2009.87
|View full text |Cite
|
Sign up to set email alerts
|

Most primary adrenal lymphomas are diffuse large B-cell lymphomas with non-germinal center B-cell phenotype, BCL6 gene rearrangement and poor prognosis

Abstract: Primary adrenal lymphoma is extremely rare, accounting for o1% of non-Hodgkin lymphomas, and lymphomaassociated chromosomal translocations have yet to be reported in this entity. We performed a retrospective study of 10 cases in immunocompetent patients including 4 males and 6 females with a median age of 68 years. The most common presenting symptoms were abdominal pain and fever; unexpectedly, clinically evident adrenal insufficiency was detected only in one patient. The mean tumor size at diagnosis was 8.5 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
77
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 24 publications
(31 reference statements)
11
77
0
1
Order By: Relevance
“…We identified 8 extranodal sites that have an impact on prognosis, 7 of which are associated with a poor prognosis. Lymphomas with involvement in these sites reportedly tend toward advanced stages, [5][6][7][8][9][10][11] whether defined as primary sites or not. Patients with extranodal involvement of these sites in our cohort also tended to have disseminated disease.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 8 extranodal sites that have an impact on prognosis, 7 of which are associated with a poor prognosis. Lymphomas with involvement in these sites reportedly tend toward advanced stages, [5][6][7][8][9][10][11] whether defined as primary sites or not. Patients with extranodal involvement of these sites in our cohort also tended to have disseminated disease.…”
Section: Discussionmentioning
confidence: 99%
“…Based on univariate analysis, these authors also demonstrated that the lung, liver, spleen, kidney, and skin involvement was significant. Furthermore, isolated reports have suggested that involvement of the adrenal glands [21,22], skin [23], and kidney [24] may also be associated with a poor prognosis. Moreover, we showed that a novel extranodal scoring system, using these extranodal sites, may improve the predictability of older risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…Kyung Min Kim et al reported a series of PA-DLBCL cured through Rituximab-CHOP (R-CHOP) chemotherapy, these cases were confirmed of diagnosis through CT guided needle biopsy, and did not undergo surgery treatment [13]. Ana Mozos et al summarized 10 cases of PA-DLBCL patients, which 5 are affected bilaterally, during 4.5 months of random visitations, 7 cases died of lymphoma, 1 died of unrelated disease, 1 survived with the disease, 1 cured and survived [14]. Satoshi Ichikawa et al analyzed 7 cases of PA-DLBCL patients, 5 affected bilaterally, underwent R-CHOP chemotherapy, 2 year survival rate was 57% [15].…”
Section: Treatmentmentioning
confidence: 99%